Brazilian Market Portfolio - Tessari, Cristina; Meyer-Cirkel, Alexis (Washington, D.C. : International Monetary Fund, 2017)
In recent years, Brazil has achieved substantial progress in capital market development by building a diversified investor base and expanding the menu of available financial instruments. In this context, we evaluated the invested Brazilian market portfolio for a period spanning 2005-15. This is a portfolio of all assets proportionally weighted by their market capitalization, and it is divided in eight broad categories: government bonds, equities, bank funding bonds, corporate bonds, real-estate, agribusiness, private-equity, and credit bonds. While the paper focuses on stylized facts related to market size, composition weighting and changes over time, the estimated market portfolio contains important information for policy makers and market participants alike.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet